Perawatan Payudara pada Ibu Menyusui di Posyandu Kopi Wilayah Kerja Puskesmas Anggut Atas - Lety Arlenti; Rismayani Rismayani; Lolli Nababan; Rara Oktavia; Chikita Mayumi (JURNAL BESEMAH, 2022)
The purpose of this counseling is to increase the knowledge of cadres and mothers who have babies about the benefits of breast care. The method used in this service is counseling and practice which is carried out at the Posyandu Kopi, the Work Area of ​​the Anggut Atas Health Center. The results of this training and counseling are cadres and mothers, increasing knowledge about breast care and the importance of breast care to increase milk production and maintain breast hygiene. Cadres and mothers can do breast care themselves at home and teach the community later.